O Programa Institucional de Bolsas de Iniciação à Docência (PIBID) na formação inicial de professores no curso de licenciatura em Geografia, Cajazeiras-PB - Almeida, David Luiz Rodrigues de (2020)
This work investigates the initial training of geography teachers participating in the Institutional Program for Teaching Initiation Scholarships (Pibid). Pibid is a public initiative that aims to contribute to the process of teacher training from the articulation between university and school, theory and practice, offering a greater experience of school practice by undergraduate students. This program was instituted in 2007; however, only with the Capes Notice number 61/2013 that the geography subproject was started at the Teacher Training Center (CFP) of the Federal University of Campina Grande (UFCG), campus Cajazeiras-PB, place of this investigation. The participants of this research are: four undergraduate students in geography (Pibid scholarship students), two Basic Education teachers (supervising teachers) and two Higher Education professors (one geography professor coordinator and the other one, an educational management coordinator). The general objective of the research is to analyze the Pibid contribution to the development of a knowledge base for the teaching of scholarship students of the licentiate degree in geography at UFCG, CFP, Cajazeiras-PB campus. This research has a qualitative approach. The discourse analysis procedure was used to ascertain the discursive formations, parameters and rules presented by the normative guidelines of the Coordination for the Improvement of Higher Education Personnel (Capes), reports, scientific productions and others. The imaginary formations of Pibid scholarship students, supervising teachers and coordinators are also examined based on the interviews. From the studies by Lee S. Shulman, the knowledge base used for the initial training of geography teachers is analyzed, being composed of four main categories: theme knowledge, pedagogical knowledge, context knowledge and pedagogical content knowledge (PCK) of geography. The results of this investigation demonstrate how knowledge and pedagogical reasoning transform knowledge into teaching, generating a broad understanding, errors and misunderstandings. Although the discursive formations indicate a relational pedagogy and an epistemology of critical or constructivist geography, there are different theoretical and methodological conceptions involved in the Pibid interventions. According to the research subjects, sources of knowledge are registered in the program: school practice, didactic and scientific materials, research and the participation in the Pibid political life. The subjects present a polysemic discourse on the understanding of Pibid theory and practice, with three interpretations: organization of the pedagogical work, pedagogical dimension and school knowledge construction of the content. Despite the importance given by Shulman and his collaborators to the PCK category, context knowledge presents itself as an essential element throughout the teaching process. It articulates knowledge to manage the classroom, understanding regarding the school community and the place. In addition to this, it attributes meaning to the teachers' training act and changes the perception on the contents, influencing the way it will be approached at school.